A REGULATED REGARD: COMPARING THE GOVERNANCE OF ANIMAL AND HUMAN EXPERIMENTATION - Black, Vaughan (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2011)
Discussion about animal welfare often give rise to observations to the effect that animals are treated differently than humans. Typically these remarks take the form of noting that animals are treated worse than humans are and moreover that law and other regulatory mechanisms permit and facilitate this. In the context of research, however, one sometimes encounters assertions that animals are treated better than humans are and that regimes for the regulation and oversight of such research reinforce this. This paper looks at several examples of the latter form of assertion. It finds them grossly false and goes on to explore why such farcically inaccurate statements continue to proliferate.